Biological and Pharmacological Activity of Plant Natural Compounds III (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
By joining the two previous editions, this Special Issue completes the trilogy of Special Issues entitled "Biological and Pharmacological Activity of Plant Natural Compounds", which deal with the properties and effects of phytonatural products in preclinical models. This third edition has also remained focused on their therapeutic potential, with the aim of increasing and contributing to the expansion of our scientific knowledge on plants in human health. We hope readers will enjoy this Special Issue as much as the previous publications.